Elucidating Inorganic Nanoscale Species in Solution: Complementary and Corroborative Approaches. Issue 12 (24th April 2013) - Oliveri, Anna F.; Elliott, Edward W.; Carnes, Matthew E.; Hutchison, James E.; Johnson, Darren W.
Abstract The challenge of defining a length on the nanoscale is non‐trivial. For a well‐defined inorganic nanoscale species, a size measurement can describe a number of different dimensions (core, shell, solvation sphere). Often size is reported out of context or even inadvertently misrepresented. Since many of the techniques used to measure size depend on significant and sometimes destructive sample preparation, an additional challenge is defining "what size means" for a nanoscale species in solution. In this Concept, the distinction is made between complementary techniques that can be used together to unveil more information about the material in question, and corroborative techniques, which are used to make multiple measurements of the same property. Additionally, corroborative techniques can be used to measure the same property in and out‐of solution so as to reveal details about solution behaviour. We highlight various approaches to this characterization challenge in the context of three case studies that demonstrate the use of both complementary and corroborative techniques to elucidate the various functional dimensions of different types of inorganic nanoscale species in solution.